CORPORATE GOVERNANCE IMPLEMENTATION AND PERFORMANCE ASSESMENT USING THE CGCG’s UGM RATING MODEL: COMMERCIAL BANKS IN INDONESIA - Arika Artiningsih; M. Ridwan Novmawan; Sony Warsono (Journal of Indonesian Economy and Business (JIEB), 2011)
The purpose of this research is to examine the implementation of Good Corporate Governance (GCG) in Commercial Banks before and after the policy of The Bank Indonesia Regulation (PBI) Number 8/4/PBI/2006 concerning Good Corporate Governance Implementation for Commercial Banks. Center for Good Corporate Governance Universitas Gadjah Mada (CG CGCG UGM) rating model was employed to measure CG implementation in Commercial Banks which calculate both company organs and Corporate Governance (CG) basic principles in a universal framework. From the company organs perspective, a CG system consists of five (5) organs interacting each others, which are board of directors, board of executives, boards of commissioners/committees, auditors, and stakeholders. Meanwhile, from the CG basic principles perspective, a CG system should fulfill five (5) CG principles, which are Transparency, Accountability & Responsibility, Responsiveness, Independency, and Fairness. Therefore, the CG framework and rating model use The information technology as the main pillar in the application of CG. As for measuring banking performance, CAMEL ratio--which consist of the Capital Adequacy Ratio (CAR), Non Performing Loan (NPL), Management (Man), Net Interest Margin (NIM), and Loan to Deposit Ratio (LDR)--was applied. In conclusion, Using CGCG UGM rating model, it is discovered hat CGimplementation at Indonesian banking system was improved subsequently to the issuance of PBI. Whereas on its performance, the significant changes were indicated by only two ratios, i.e. LDR and MAN. This research depicts Bank Indonesia effectiveness as regulator at providing CG implementation guide on PBI. This research reveals for the urge for Indonesian banking industry to boost GCG implementation for their rating and performanceimprovement. Keywords: corporate governance asessment, CAMEL, commercial banks, corporate governance